Аssessment and prediction of flood risks in river basins - Petrochenko, Oleksiy V. (Kyiv National University of Construction and Architecture, 2020)
The problem of floods is considered as an essential component of the modern global problem of water on the planet. Given the structural complexity of the flood problem and the urgent need to address it in Ukraine, the need and feasibility of creating a perfect methodology for integrated flood risk management in river basins has been stated. It is noted that an important component of the methodology of integrated flood risk management in river basins is flood assessment and forecasting. The article is devoted to the development of scientific and methodological foundations for assessing and forecasting flood risks in river basins. Floods are classified according to their intensity. Two main types of flood protection in river basins are distinguished – situational and preventive. A criterion is given by which it is advisable to choose the type of flood protection in river basins. Depending on the type of flood protection chosen, flood protection measures are divided into situational and preventive. A fundamental approach to the management of flood protection of a situational type is provided, according to which short-term forecasting of the flood and the subsequent implementation of response measures during the approach, passage and completion of the flood are provided. The basic principles of flood control of a preventive type are described, according to which long-term forecasting of floods and the implementation of response measures through the construction and operation of flood control structures is provided. It was noted that there were no perfect methods for long-term flood forecasting, in connection with which an attempt was made to develop a fundamentally new flood forecasting methodology, which is based on the use of statistical data on past flood situations. It is proposed to perform long-term flood forecasting according to hydrological indicators of floods and indicators of their consequences. The long-term flood forecasting technique is based on the approximation of the flow rate of the water flow and the total flood losses in the form of descending hyperbolic functions depending on the flood intensity. The main result of long-term flood forecasting is the amount of total flood damage projected for the next 99 years that is found by integrating the flood loss function. Predicted flood losses form the basis of the dependencies for determining the main indicators of the effectiveness of preventive flood control measures – the average annual prevented damage and damage prevented during the estimated life of protective structures.